Gambaran Mekanisme Koping dan Kecemasan Menyusun Skripsi pada Mahasiswa Keperawatan - Argi Umbu Dena Gaba; Miftakhul Ulfa; Ahmad Guntur (Media Husada Journal Of Nursing Science, 2026)
ABSTRACT Gaba, Argi Umbu Dena. 2024. Overview of Coping Mechanisms and Anxiety in Thesis Preparation among Nursing Students of STIKES Widyagama Husada Malang. Thesis. Nursing Education Study Program of Widyagama Husada Malang School of Health Science. Advisors: 1) Miftakhul Ulfa, S.Kep., Ns., M.Kep 2) Ahmad Guntur A., S.Kep., Ns., M.Kep Background: A thesis is a scientific writing based on research results from the field or literature studies, prepared by students in accordance with their study program or field. The complexities that students experience in writing their theses can lead to psychological disturbances. Objective: To find out the overview of coping mechanisms and anxiety in thesis preparation among Nursing students at STIKES Widyagama Husada Malang. Methods: This study used a quantitative descriptive design. The population consists of all seventh-semester Nursing students at STIKESWidyagama Husada Malang, totaling 34 respondents using a Total Sampling technique. Data collection was conducted online using a questionnaire on coping mechanisms and anxiety in September 2024, which was then analyzed using descriptive statistics. Results: The majority of respondents, totaling 25 individuals (73.5%), employed adaptive coping mechanisms, which helped them manage academic stress more effectively. However, 9 respondents (26.5%) were found to use maladaptive coping strategies. In terms of anxiety levels, most students experienced moderate anxiety (19 respondents or 52.9%) and mild anxiety (15 respondents or 44.1%). No students were found to experience severe anxiety. Conclusion: The majority of respondents are 22 years old (12 respondents or 35.3%), with the youngest being 20 years old (1 respondent or 2.9%). A total of 25 respondents (73.5%) use adaptive coping mechanisms, while 9 respondents (26.5%) use maladaptive coping mechanisms. The anxiety levels are mostly in the moderate category (19 respondents or 52.9%) and mild (15 respondents or 44.1%), with no respondents reporting severe anxiety. References : 23 references (2016-2024) Keywords : Coping Mechanisms, Anxiety, Thesis